ISOLATION OF STROMAL VASCULAR FRACTION FROM VASCULAR TISSUES (2014)
Methods of isolating stromal vascular fractions for use in human subjects from a tissue comprising a blood vessel using mechanical, optionally ultrasonic cavitation, enzymatic, and/or chemical methods are provided. These methods yield an increased number of the cells which constitute the stromal vascular fractions (about 10-fold greater) than methods which use collagenase to isolate these cells. The stromal vascular fraction may be isolated from any tissue that comprises blood vessels, for example, muscle and adipose tissue. Additionally, the tissue may be isolated obtained from nonliving sources and animals (e.g., postmortem).